PENGEMBANGAN MEDIA INTERAKTIF BERBASIS DIGITAL PADA MATERI METAMORFOSIS MAKHLUK HIDUP DALAM MATA PELAJARAN IPAS KELAS III SD NEGERI 3 PAYUNG - Sri Ainantia; Yuanita; Feri Ardiansah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study addresses the underutilization of learning media, which predominantly relies on traditional textbooks. This approach often leads to a focus on reading rather than a comprehensive understanding of the subject matter. The availability of internet access among students serves as a valuable resource for implementing digital-based interactive media in the context of teaching metamorphosis concepts. The primary objective of this research is to develop digital interactive media that are both valid and practical, and to assess their effectiveness in enhancing students’ comprehension of the metamorphosis of living things. This research adopted a Research and Development (R&D) framework based on the ADDIE development model. The study sample consisted of third-grade students from SD Negeri 3 Payung. Data collection methods included interviews, questionnaires, and assessments, specifically pretests and posttests. Data analysis focused on evaluating the validity, practicality, and potential impact of the developed media. The results from the media validity assessment indicated an 88% rating from material experts and an 86% rating from media experts, both classified as “very valid.” The practicality assessment yielded a rating of 98% in small groups, 92.2% in large groups, and a full approval rating of 100% from educators, all categorized as “very practical.” Furthermore, the paired sample t-test results demonstrated a significance level of 0.000 (2-tailed), indicating a statistically significant difference between pretest and posttest scores. Additionally, the media showed a potential effect value of 0.76, categorized as “high.” Thus, the digital-based interactive media developed for the subject of metamorphosis of living things in the IPAS curriculum for Grade III at SD Negeri 3 Payung is recognized as effective in improving students’ understanding and academic performance.